Analysis of institutional governance model regulation: case study of the tourism zone sezs - Rian sacipto; Diana ma'rifah; Azmi anisah; Hasna fadhilah (Journal of Law Science, 2023)
The method used in this research is a qualitative approach supported by an empirical juridical analysis approach by collecting data through observation and interviews. The results of the research are expected to be able to formulate a model of governance of authority, human resources and governance arrangements related to policies for the development of Special Economic Zones in Indonesia. the evaluation of the development and management of SEZ by the SEZ National Council based on the progress of its development is strengthening various aspects and sectors in supporting SEZ, which determines how it is realized in terms of effectiveness and efficiency in order to accelerate the achievement of national economic development, it is necessary to increase investment in the focus of tourism research that will be carried out by team through setting up regulations, governance,